Correlation between invasive mammary carcinoma grade and size in ultrasound‐guided core needle biopsy and subsequent surgical excision. Issue 4 (19th December 2017) - Podoll, Mirna B.; Straub, Melissa; David, Stephanie N.; Desouki, Mohamed Mokhtar
Abstract: The purpose of this study was to correlate the histologic grade, mitotic rate and size of invasive mammary carcinomas (IMC) on ultrasound (US) core needle biopsy (CNB) and the follow‐up excision (FUE). The underestimation and overestimation of the grades by CNB were 11% and 8%. CNBs were more specific for grade 3 tumors. Tumors >10 mm by US examination showed greater concordance in grades. The size in the FUE was the best determinant of pT followed by US examination. The extent of IMC on CNB was larger than FUE in 8% resulting in pT upstaging in 3% of cases.